Analysis of the Implementation of E-Learning Communication Technology in Higher Education - Nabillah (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study discusses the use of e-learning communication technology in higher education. The method used in this article is qualitative research with library research, namely research whose subjects are literature. A large amount of facts and data in qualitative research are believed to be stored in the form of documents. Most of the available data is in the form of letters, notes, reports, photographs, and so on. The results obtained in this study are that the implementation of e-learning has the potential to enhance the learning experience, but also faces challenges that need to be addressed. Educational institutions need to consider these advantages and disadvantages to design effective and inclusive e-learning programs and provide the necessary support for students to succeed in a digital learning environment.